2021
DOI: 10.1111/echo.15042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular myocardial mechanics in patients with normally functioning bicuspid aortic valves: A systematic review and meta‐analysis

Abstract: BackgroundStudies have found conflicting results concerning the left ventricular (LV) myocardial deformation properties in patients with normally functioning bicuspid aortic valves (BAVs). Whether the remodeling process of LV occurs independently in patients with BAV is a matter of debate.MethodWe searched PubMed, Embase, Cochrane library, and Web of Science for cohort studies aiming to assess LV function in adults with isolated BAV compared with tricuspid aortic valve (TAV) controls. Standard mean difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…11,[32][33][34] In line with the findings of the present study, several others have found a higher LV mass and subclinical LV dysfunction in young patients with BAV, suggesting that the compensatory concentric remodeling process begins early in life. 10,35 A future large longitudinal study that follows patients with BAV from an early age and forward might give us information about when adverse LV remodeling is initiated and how it is affected by aortic valve degeneration. Furthermore, analyzing LV structure and function in different age groups of patients with BAV referred for AVR could also potentially support the concept of an age-dependent adverse LV remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[32][33][34] In line with the findings of the present study, several others have found a higher LV mass and subclinical LV dysfunction in young patients with BAV, suggesting that the compensatory concentric remodeling process begins early in life. 10,35 A future large longitudinal study that follows patients with BAV from an early age and forward might give us information about when adverse LV remodeling is initiated and how it is affected by aortic valve degeneration. Furthermore, analyzing LV structure and function in different age groups of patients with BAV referred for AVR could also potentially support the concept of an age-dependent adverse LV remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Data from several cross-sectional studies suggest that adolescents and young adults with a BAV show early signs of adverse structural LV remodeling even in the absence of valvular dysfunction. 10 Consequently, impaired LV function is more common in individuals with BAV compared with age- and sex-matched TAV controls, and is probably related to a chronically elevated afterload attributable to eccentric aortic valve opening and decreased ascending aortic elasticity. 11 , 12 In longitudinal studies, it has been shown that individuals with BAV exhibit a higher risk of premature congestive heart failure (HF) than the general population.…”
mentioning
confidence: 99%
“…Interestingly, in patients with BAV and no ascending aortic dilatation, GWW increased and GWE decreased as compared with controls, although the aortic diameter and aortic stiffness index were similar. These findings offer a novel perspective of BAV as being not only a valvulo-aortopathy disease but also a form of cardiomyopathy ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 89%